Analysis of the Eucalyptus Crown of Clone IND 72 and IND 83 Against the Composition of Undergrowth Vegetation in PT.Toba Pulp Lestari Tbk., Habinsaran Sector of Toba Regency - Nurrachmania, Meylida; Rozalina, Rozalina (Universitas Labuhanbatu, 2022)
The purpose of the study was to identify the diversity of plant types under the Eucalyptus stand and analyze the percentage of cover titled Eucalyptus Clone IND 72 and 83 against the composition of the undergrowth vegetation species in the Habinsaran sector of Toba Regency.Plot determination is done using the minimum species curve method, so that the number of PLOTS IND 72 as many as 29 plots, and IND 83 as many as 28 plots.The data taken is data on the vegetation of the undergrowth vegetatioin the form of the number and type of undergrowth vegetatio, as well as header cover data, then analyzed by calculating density, frequency, INP, and Similarity Index. There are 10 types of lower plants located in the Habinsaran Sector TPL Plant Forest of Toba Samosir Regency.The dominance of the undergrowth vegetation of each clone is occupied by boreria sp type with Important Value Index (INP) on the Stands of Eucalyptus Clone IND 72 = 67.19, and Stands Eucalyptus Clone IND 83 = 57.68.In the stands of Eucalyptus Clone IND 72 obtained a percentage of headers of 1.70% (<50%) including the category of small header cover, with a composition of undergrowth vegetation as many as 9 types, with an average density of 128.9 / ha.On the stand of Eucalytus Clone IND 83 obtained a percentage of headers of 1.80% (<50%) including the category of small header cover, with a undergrowth vegetation as many as 10 types, with an average density of 104.6/ha.